Comparative Karyomorphological Analysis of Four Bari Released Germplasms of Garlic - Ferdousi, Roksana; Saha, Susmita; Begum, Kazi Nahida (Journal of the Asiatic Society of Bangladesh, Science, 2020)
Abstract not available J. Asiat. Soc. Bangladesh, Sci. 46(2): 215-220, December 2020